Online midcourse guidance method for boost phase interception via adaptive convex programming - Yang, Biao; Jing, Wuxing; Gao, Changsheng (Aerospace science and technology, 2021)
This paper proposes an online midcourse guidance method for boost phase interception. Dynamic models are established and flight constraints are analyzed firstly. Handover constraints between midcourse and terminal guidance are transformed as an optimization problem by introducing additional optimization variables in this paper. Then midcourse guidance problem can be transformed as an optimization problem with constraints. It can be solved by convex programming through constraints relaxation and linearization. In order to overcome flight uncertainty and changes of target trajectory, an online guidance framework based on convex programming is presented. But it takes some calculation time to solve the convex programming problem, which causes the delay of guidance commands. Based on sensitivity analysis of nonlinear programming, a command correction method is designed to reduce the delay effect. Besides, an adaptive update strategy of trust region in convex programming is proposed to guarantee calculation accuracy and speed. And the discrete points are continuously updated with the flight time to improve calculation efficiency. Finally, numerical simulations for different cases have demonstrated the effectiveness of the online midcourse guidance method proposed.